Integrating Stochastic and Deterministic Process in the Biogeography of N2-Fixing Cyanobacterium Candidatus Atelocyanobacterium Thalassa - Li, Liuyang; Wu, Chao; Huang, Danyue; Ding, Changling; Wei, Yuqiu; Sun, Jun (Frontiers in Microbiology, 2021)
UCYN-A is one of the most widespread and important marine diazotrophs. Its unusual distribution in both cold/warm and coastal/oceanic waters challenges current understanding about what drives the biogeography of diazotrophs. This study assessed the community assembly processes of the nitrogen-fixing cyanobacterium UCYN-A, developing a framework of assembly processes underpinning the microbial biogeography and diversity. High-throughput sequencing and a qPCR approach targeting the nifH gene were used to investigate three tropical seas: the Bay of Bengal, the Western Pacific Ocean and the South China Sea. Based on the neutral community model and two types of null models calculating the β-nearest taxon index and the normalized stochasticity ratio, we found that stochastic assembly processes could explain 66–92% of the community assembly, thus they exert overwhelming influence on UCYN-A biogeography and diversity. Among the deterministic processes, temperature and coastal/oceanic position appeared to be the principal environmental factors driving UCYN-A diversity. In addition, a close linkage between assembly processes and UCYN-A abundance/diversity/drivers can provide clues for the unusual global distribution of UCYN-A.